Modulation of the photobehavior of gefitinib and its phenolic metabolites by human transport proteins - Lorena Tamarit; Lorena Tamarit; Meryem El Ouardi; Meryem El Ouardi; Emilio Lence; Inmaculada Andreu; Inmaculada Andreu; Concepcion González-Bello; Miguel A. Miranda; Miguel A. Miranda; Ignacio Vayá; Ignacio Vayá (Frontiers Media S.A., 2024)
The photobiological damage that certain drugs or their metabolites can photosensitize in proteins is generally associated with the nature of the excited species that are generated upon interaction with UVA light. In this regard, the photoinduced damage of the anticancer drug gefitinib (GFT) and its two main photoactive metabolites GFT-M1 and GFT-M2 in cellular milieu was recently investigated. With this background, the photophysical properties of both the drug and its metabolites have now been studied in the presence of the two main transport proteins of human plasma, i.e., serum albumin (HSA) and α1-acid glycoprotein (HAG) upon UVA light excitation. In general, the observed photobehavior was strongly affected by the confined environment provided by the protein. Thus, GFT-M1 (which exhibits the highest phototoxicity) showed the highest fluorescence yield arising from long-lived HSA-bound phenolate-like excited species. Conversely, locally excited (LE) states were formed within HAG, resulting in lower fluorescence yields. The reserve was true for GFT-M2, which despite being also a phenol, led mainly to formation of LE states within HSA, and phenolate-like species (with a minor contribution of LE) inside HAG. Finally, the parent drug GFT, which is known to form LE states within HSA, exhibited a parallel behavior in the two proteins. In addition, determination of the association constants by both absorption and emission spectroscopy revealed that the two metabolites bind stronger to HSA than the parent drug, whereas smaller differences were observed for HAG. This was further confirmed by studying the competing interactions between GFT or its metabolites with the two proteins using fluorescence measurements. These above experimental findings were satisfactorily correlated with the results obtained by means of molecular dynamics (MD) simulations, which revealed the high affinity binding sites, the strength of interactions and the involved amino acid residues. In general, the differences observed in the photobehavior of the drug and its two photoactive metabolites in protein media are consistent with their relative photosensitizing potentials.